New developments in legal reasoning and logic from ancient law to modern legal systems - Rahman, Shahid 1956-; Armgardt, Matthias 1968-; Kvernenes, Hans Christian Nordtveit (Springer, 2022)
Part 1. Historic Roots -- 1. What is to have Knowledge of Roman Legal Methods and Reasoning? (Geoffrey Samuel) -- 2. The Use of Logic for Creating Fact Patterns in Roman Legal Writings (Markus Winkler) -- 3. A Logical Framework for The Islamic Law (Mohammad Ardeshir & Fatemeh Nabavi) -- 4. The Formal Evolution of Islamic Juridical Dialectic: a Brief Glimpse (Walter Edward Young) -- 5. Independent Reasoning in Law: The Jewish Tradition (Joseph E. David) -- Part 2. Contemporary Law -- 6. Rethinking Interpretative Arguments (Hális Alves do Nascimento França) -- 7. A Logic for the Interpretation of Private International Law (Alessandra Malerba, Antonino Rotolob, and Guido Governatori) -- 8. A Formal Model for Analogies in Civil Law Reasoning (Matthias Armgardt) -- 9. Approaching an Analysis of Reasoning by Analogy (Hans Christian Nordtveit Kvernenes) -- 10. Elements for a Dialogical Approach on Parallel Reasoning. A Case Study of Spanish Civil Law (Maria Dolors Martínez -Cazalla; Tania Menéndez-Martín) -- 11. Abductive Inference in Legal Reasoning: Resolving the Question of Res Ipsa Loquitur’s Procedural Effect (Douglas Lind) -- Part 3. Deontic Logic, Legal Reasoning, Normativity) -- 12. Common Law Precedent and the Logic of Reasons (Federico L.G. Faroldi) -- 13. Reasoning with Rules and Rights: Term-Modal Deontic Logic (Stef Frijters & Joke Meheus; Frederik Van De Putte") -- 14. Dyadic Deontic Logic in HOL: Faithful Embedding and Meta-Theoretical Experiments (Christoph Benzmüller, Ali Farjami, and Xavier Parent) -- 15. On the Role of Past Treatment of Terms From Written Laws in Legal Reasoning (Jaromir Savelka; Kevin D. Ashley) -- 16. Jørgensen’s Dilemma in the interface between Legal Positivism and the Natural Law tradition (Juliele Maria Sievers) -- 17. Coping with inconsistencies in legal reasoning (Max Urchs)
Keywords: Rechtsphilosophie; Juristische Argumentation; Logik; Rechtssystem; Logic; Law—Philosophy; Law; Political science; Artificial intelligence; Computer logic; Computers; Law and legislation; Logic design; Aufsatzsammlung